Scientific method and human dignity in the balance - Bennett, D.G. (Universiti Putra Malaysia, 2014)
This paper is the third in a series exploring the strengths and weaknesses of Bloom's Taxonomy of Learning Objectives. The first paper (Cracks in Bloom's Taxonomy at 60) looked at ambiguities. My other paper (What is the 'Whole Thing"?) looked at potential upgrades and room for improvement. This article looks at the current damage being done in the hard sciences for lack of an adequate template of systematic learning. Two articles on Darwin's Theory of Evolution are scrutinised for the same ambiguities, vagueness and gaps in logic as are found in Bloom's Taxonomy. How, where and why the gaps should be filled in is presented in this article, and potential upgrades for Bloom's Taxonomy are illustrated with suggested examples and illustrations. The centerpiece of our article is a pair of articles from mainstream, accomplished and credible sources, National Geographic and the American Association for the Advancement of Science. Our argument is launched upon the equivocation and conflation between "descent with modification" and "natural selection.". Â© Universiti Putra Malaysia Press.